POTENTIALS RAILWISE PROPAGATION STUDY - Yashchuk, K. I. (Science and Transport Progress, 2017)
Purpose. To conduct the study of the potentials and currents propagation along the rails to evaluate the potential difference and the current asymmetry in the rails that may have an impact on the work of railway automatics and supervisory systems. Methodology. To compass the purpose, the author applies methods of analysis and synthesis of track circuit electrical engineering calculations, mathematical modeling and methods of homogeneous and heterogeneous ladder circuits. Findings. TheconductedtheoreticalstudiesindicatethatinthemountainoussectionsofDCtractionrailwaysthereareveryhigh-levelcurrents,wherebyevenatnominalasymmetryratio theasymmetrycurrentwill beunacceptablyhigh.The re-equipment of running line with the automatic blocking system with tonal rail circuits resulted in reduction of the number of impedance bonds, the equalizing functions of which required further advanced research, that allowed obtaining the potential railwise propagation curves when installing the impedance bonds every 6 and 5 km. The resulting potential difference was too high for railway automation systems, so the potential propagation study was conducted with impedance bonds placed every 3 and 3.5 km, which greatly improved the operation conditions of track circuits. Originality.The proposed method for calculating the propagation of potentials and currents in the rail network of DC traction line is characterized by the representation of the common ladder circuit of each rail as a series of T-shaped four-poles connected in cascade, taking into account the grounding of the contact-line supports on the nearer rail. It has allowed estimating the levels of asymmetry currents that branch into the equipment of track circuits and have a negative impact on their operation. Practicalvalue. The obtained results can be used in designing and re-equipping the running lines with new railway automatics and supervisory systems, as well as for evaluating the influence of high asymmetry currents on the railway automation systems operation.